THE ROLE OF ISLAMIC FINANCE ORGANIZATIONS IN THE DEVELOPMENT OF ECONOMIC SECTORS IN UZBEKISTAN - Sattarova Dilfuza Dilshodbekovna (American Journals, 2025)
The article reflects the content of Islamic finance, the areas of activity of Islamic finance organizations, and the possibilities of increasing the efficiency of economic sectors through the development of Islamic finance in Uzbekistan.
Keywords: Islamic finance, IDB, financing methods, SWOT analysis, “Uzbekistan 2030” strategy.